Answers

2014-11-20T17:37:44+05:30
This method may be difficult but it was thought in ma school days
2y ^2 + 21 = 13y
2y^2 + 21 -13y
2y^2 - 13y + 21
multiply 2 with 21 we get 42 
then the equation be y^2 - 13y + 42 
let factorise we get 
[( 2y - 7 ) ( 2y -6)]/ 2
[ (2y-7) 2( y-3) ]/2                          taking 2 common outside and divide with 2 
(2y-7) ( y -3) = o 
2y =7 ; y =3
y = 7/2 and y = 3
0
2014-11-20T18:29:15+05:30
2 y^{2} +21 = 13y


2y^2-13y+21=0

By factorisation,

2y^2-7y-6y+21=0

y(2y-7)-3(2y-7)=0

(y-3)(2y-7)=0

y-3=0                   
            2y-7=0

y=3                2y=7
 
                                   y= \frac{7}{2}

Therefore, y= 3 or  \frac{7}{2}


0